How Gaps in traceability systems affect Uganda’s livestock sector transformation - Private Sector Development Unit Ministry of Finance, Planning and Economic Development (Economic Policy Research Centre, 2021)
Strong livestock traceability systems are critical for transforming Uganda’s livestock sector and economy. Using desk reviews and key informant interviews, the findings show that while Uganda has an appropriate legal and regulatory framework governing the entire livestock value chain, traceability rarely emphasised, nor is it highly visible. Violation of bilateral and regional agreements concerning livestock products partly hinges on the significant weakness or lack of traceability systems in the sector, an essential requirement in trade and ensuring food safety and standards. This brief recommends fast-tracking the instituting of traceability systems and reviewing the old legal frameworks that govern the sector for the envisaged transformation as emphasised in the NDPIII’s agro-industrialisation programme.